PENGARUH ANTESEDEN KEPUASAN DAN LOYALITAS PASIEN RAWAT INAP DI RUMAH SAKIT DHARMA KERTI TABANAN - Ariani, A.A. Sg. Ani; Rahyuda, Ketut; Suprapti, Ni Wayan Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.10.TAHUN 2016, 2016)
This study aims to investigate the influence of service quality and fairness of the price of the trust, determine the effect of trust on satisfaction and loyalty relationship with patient inpatient hospital Dharma Kerti. The population in this study were patients who never felt inpatient services at hospitals Dharma Kerti. The sample was 175 respondents using purposive sampling sampling technique. Data processing and hypothesis testing in this study used analysis techniques Structural Equation Modelling (SEM) using AMOS 16 and SPSS Statistics 17.0. The results showed that 1) Quality of service is significant positive effect on confidence, 2) Fairness price significant positive effect on trust, 3) Belief significant positive effect on satisfaction, 4) Customer satisfaction significant positive effect on loyalty. Recommended to the Management of RS Dharma Kerti always strive to maintain and improve service quality, especially aspects of responsiveness, reliability and empathy, so it can be featured on the service in the hospital.
Keywords: Service Quality, Fairness Price, Trust, Satisfaction, Customer Loyalty